Game on. (Economist, 2009)
The article focuses on Howard Stringer, Chief Executive Officer (CEO) of the household electronics company Sony. The company is expected to report a loss of almost $3 billion in 2008 and has no profitable product lines. Stringer has used these problems to institute a sweeping reorganization of the firm, making large layoffs and centralizing operations including computer software development.